Vemurafenib as first-line therapy in BRAF-V600E-mutant Erdheim-Chester disease with CNS involvement. Issue 11 (19th November 2019) - Fernández-Eulate, Gorka; Muñoz-Lopetegi, Amaia; Ruiz, Irune; Urtasun, Miguel
Abstract : Erdheim-Chester disease (ECD) is a rare histiocytosis that may affect the central nervous system (CNS). Infiltration by the disease occurs throughout the neuroaxis, usually involving the dentate nucleus and the pons, manifested as a pyramido-cerebellar syndrome. CNS involvement is an adverse prognostic factor which warrants prompt evaluation and treatment. BRAF mutation occurs in more than half of the cases and has become central in the therapeutic approach. There is rapidly growing evidence that BRAF inhibitors such as vemurafenib or dabrafenib are effective in treating CNS-spread disease. We present a patient with BRAF -V600E-mutant ECD with a classical pyramido-ataxic onset of disease who improved after prompt diagnosis with vemurafenib treatment as first-line therapy.